Thermal and deformation analysis of joint interfaces in machine tools - Gashi, Bekim (Cranfield University, 2008)
Machine tools are made up of many different parts connected together. In order to understand and create more accurate thermal and deformation numerical models the heat transfer characteristics of machine tool interfaces need to be understood. Previously heat transfer across interfaces has not been incorporated in finite element models in thermal and deformation analysis of machine tools. To a varying degree the issue of interfaces will have an effect on the overall performance of machine tools, and clearly if not considered and resolved at the strategic design stage they may be difficult and expensive to correct, once machine tools are operational. An inability to adequately understand and model the interfaces in machine tools is therefore a major limitation to current knowledge. In this research programme heat transfer and corresponding thermal deformation of metal blocks in contact having pre-defined interface geometries, were experimentally and numerically investigated. Factors such as the contact pressure, the contact conformance, and the interface material were investigated. It was found that the most influential factors were contact pressure and contact conformance. Interface material was also found to have a bigger influence if the contact area was non-conforming. When interface material was thicker than the surface roughness, the heat flow across the interface was reduced as fewer contact asperities came into contact. In order to optimise modelling it was necessary to optimise the convection coefficient - this was found to have an effect on overall heat transfer across the interface. It was also found that the overall contact area is important and not the spread of contact regions for the same overall contact. This was investigated using two different contact geometry arrangements. The numerical prediction of heat transfer across an interface is accurate if the contact is conforming. However, if the contact is non-conforming an accurate prediction is not possible. This is due to the fact that direct modelling of non-conformance is not achievable. It was found that the most influential factor on thermal deformation is contact pressure, on the other hand factors such as interface material and interface geometry showed very little effect.